2010
DOI: 10.1007/s10681-010-0260-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity and association mapping of quantitative traits in Tibetan wild and worldwide originated barley (Hordeum vulgare L.) germplasm

Abstract: Molecular diversity of 40 accessions of Tibetan wild barley (TB), 10 Syrian (SY), 72 North American (NA), 36 European (EU), 9 South American (SA) and 8 Australian (AU) varieties were characterized using multiple microsatellite loci. The 42 SSR primers amplified 278 alleles across the 175 barley accessions tested in the present study. The average gene diversity for the whole sample was 0.3387 whereas the mean value for the each population was as follows: TB = 0.3286, SY = 0.2474, EU = 0.299, AU = 0.2867, NA = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 50 publications
0
22
1
Order By: Relevance
“…In addition, BLAST search in GenBank (http://www.ncbi.nlm.nih.gov/genbank/) showed that HSP17.8 exhibited nucleotide sequence homology to a barley EST (GenBank accession AL510041) that was located in 63.4 cM on chromosome 4H [56]. Several previous studies also reported chromosome 4H had QTLs for PH [57][59], TGW [57][59], NGS [58][60], LC [61] and FLA [62]. Therefore, HSP17.8 may have cis affects for the QTLs of PH, TGW, NGS, LC, and FLA located on chromosome 4H.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BLAST search in GenBank (http://www.ncbi.nlm.nih.gov/genbank/) showed that HSP17.8 exhibited nucleotide sequence homology to a barley EST (GenBank accession AL510041) that was located in 63.4 cM on chromosome 4H [56]. Several previous studies also reported chromosome 4H had QTLs for PH [57][59], TGW [57][59], NGS [58][60], LC [61] and FLA [62]. Therefore, HSP17.8 may have cis affects for the QTLs of PH, TGW, NGS, LC, and FLA located on chromosome 4H.…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential impact of awn length on yield in barley cultivars, it is important to identify novel QTLs and genes that affect this trait. Previous genetic studies described QTLs for awn length on chromosome 3H (Chen et al 2012; Gyenis et al 2007; Wang et al 2010), possibly co-localizing with either ari - a or semi - brachytic ( uzu ) (HvBRI1); on 6HS (Sun et al 2011); close to the row type locus six - rowed spike 1 ( Vrs1 ) on 2H (Sameri et al 2006), where the awnless locus Lks1 has been mapped; on 7H (Sameri et al 2006), possibly co-localizing with either ari - f or ari - n (Druka et al 2011; Franckowiak and Lundqvist 2012); and on 7HL which is associated with DIMINUTO ( HvDIM ) (Dockter et al 2014). The majority of these studies have investigated the genetic basis of awn length differences in cultivated barley.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al (2011) reported that wild barley of Tibet displayed a higher genetic diversity than other barley subpopulations. The total number of alleles and the mean values of genetic diversity of the two-rowed wild barley from Tibet were obviously different from Israel, Iran, and Turkey (Saghai Maroof et al 1994;Ivandic et al 2002).…”
Section: Genetic Diversity Of Vrs1 Sequencesmentioning
confidence: 99%
“…Palmer et al (2009) showed that the phylogenetic tree of Vrs1 alleles separated the six-rowed barley and the two-rowed barleys and placed the Qasr Ibrim two-rowed barley within the vrs1.a1 clade. Sun et al (2011) reported that cluster analysis of 175 two-rowed and six-rowed barley accessions using multiple microsatellite loci showed no clear separation of grouping between wild barley and cultivated barley as well as a certain degree of divergence between two-rowed and six-rowed barley types.…”
Section: Evolutionary Relationships Of Two-rowed and Six-rowed Barleysmentioning
confidence: 99%